Intraductal papillary neoplasm in common bile duct opening into the stomach. Issue 2 (18th April 2020) - Lai, Victoria Cindy; Lai, Eric C.H.; Tang, Chung Ngai
Abstract: Ectopic bile duct openings are uncommonly encountered and due to limited reports, the incidence and work up are not well delineated. We therefore present our experience in the assessment and management of one such case. A 62‐year‐old lady presented with obstructive jaundice. Final investigation results revealed intraductal papillary neoplasm of the bile duct (IPNB) in an ectopic common bile duct (CBD) inserting ectopically into the lesser curve of the stomach with a normal pancreatic duct opening into the duodenum. Anatomical delineation and staging was done using computer tomography (CT) scan and endoscopic cholangiopancreatography (ERCP). Robotic distal gastrectomy, extrahepatic bile duct excision with porta lymph node dissection, and hepaticojejunostomy with Roux‐en‐Y reconstruction was performed. The blood loss and operation time were 200 mL and 301 minutes, respectively. Pathology showed IPNB with high grade dysplasia and clear margins. After transient gastroparesis, the patient recovered and was disease‐free at 1 year postoperatively. Ectopic biliary drainage into the stomach is extremely rare, but its recognition may help identify the cause of certain clinical conditions and prevent bile duct injury during surgery if required.